Stage one endometrioid endometrial adenocarcinoma: is there a role of traditional hospital follow-up in the detection of cancer recurrence in women after treatment? - Manolis Nikolopoulos (Korean Society of Obstetrics and Gynecology, 2021)
Objective To investigate the rate of asymptomatic recurrence of stage 1 endometrioid endometrial cancer and assess the role of routine hospital follow-up after treatment. Methods We performed a retrospective case-note review study of women who were diagnosed with stage 1 endometrioid endometrial adenocarcinoma at Queen’s Hospital, Romford, between January 2008 and December 2016. Results We included 299 patients with a median follow-up period of 44.4 months. All the patients underwent total hysterectomy and bilateral salpingo-oophorectomy. Adjuvant radiotherapy was offered to the patients subsequent to discussions in the multidisciplinary team meeting in accordance with the risk stratification criteria. There was no significant correlation between the risk factors and disease recurrence. In total, 11 patients presented with recurrent disease with original staging: 1a, n=6/199; and 1b, n=5/100. Four patients presented with vaginal bleeding due to vault recurrence and one patient with abdominal pain due to pelvic mass. Locoregional recurrence was an incidental finding in two other patients. Four patients presented with symptomatic distant metastases to the lung (n=2), liver (n=1), and bone (n=1). No asymptomatic recurrences were identified on routine follow-ups, despite several hospital appointments and clinical examinations. The recurrence rate for patients with stage 1a and 1b, grade 1, and grade 2 disease was 3.53%, and that for patients with stage 1a, grade 1, and grade 2 disease was 2.7%. Conclusion Routine clinical examinations have a low yield in finding recurrence in asymptomatic women and should be questioned for their value, considering the limited resources of the National Health Service (NHS). Larger studies are required to support a stratified follow-up, which will include telephone and patient-initiated follow-up.